Bioactive dibenzofurans from the rattans of Bauhinia championii (Benth.) Benth. (April 2018) - Hua, Li-Ping; Zhang, Yu-Qin; Ye, Miao; Xu, Wen; Wang, Xiao-Ying; Fu, Yan-Hui; Xu, Wei
Graphical abstract: Highlights: The constituents of the rattans of Bauhinia championii (Benth.) Benth. were investigated. Two new dibenzofurans were isolated from B. championii (Benth.) Benth. The anti-rheumatoid arthritis activities of compounds 1 and 2 were evaluated in vitro . Compounds 1 and 2 exhibited inhibitory effects with IC50 values comparable to that of methotrexate. Abstract: Two new dibenzofurans, bauhichamines A (1 ) and B (2 ), along with six known compounds (3 -8 ), were isolated from the rattans of Bauhinia championii (Benth.) Benth. (Fabaceae). The structures of1 and2 were elucidated by extensive spectroscopic methods and the known compounds were identified by comparison of their data with those reported in the literatures. All new compounds were evaluated for their anti-rheumatoid arthritis activities via examining their anti-proliferative effects on synoviocytes in vitro . Compounds1 and2 exhibited significant inhibitory effects on the proliferation of synoviocytes with the IC50 values of 103.1 ± 1.8 and 146.4 ± 1.2 μM, respectively.